Mapping Trends: Accounting System and Supply Chain Insights from Scholarly Works - Fidayanti, Anita Rohma; Fiddinia, Irta; Masuddin, Noor; Hasan, Rizqi; Rosnawati, Emy (Proceedings of The ICECRS, 2023)
This data article presents a comprehensive analysis of scholarly works on Accounting System and Supply Chain utilizing the Lens.org database. Filtering Journal articles over the last decade, we obtained 3 datasets in CSV and BiBTeX formats and extracted 9 data points for analysis. The uploaded files on Zenodo.org offer valuable insights for researchers and practitioners, aiding collaborations and further development. The data, contributed primarily by institutions like Imperial College London and authors including Trevor Hopper and Carol A Adams, spans various fields such as Business, Accounting, Economics, and Computer Science. Notably, the data reveals trends in publication volumes, active institutions, influential authors, and citation patterns. Our study sheds light on key contributors, active countries like the United Kingdom and the United States, and prominent publishers like Elsevier and Emerald. This dataset serves as a rich resource for academics and practitioners exploring Accounting System and Supply Chain dynamics, fostering future research and global collaborations.Highlights : Comprehensive Analysis: This study delves deep into scholarly works on Accounting System and Supply Chain, providing a meticulous analysis of 10 years' worth of journal articles. Global Insight: Covering data from prolific institutions like Imperial College London and authors such as Trevor Hopper, the study offers a global perspective, highlighting active countries including the United Kingdom and the United States. Citation Patterns: Revealing intriguing citation patterns, the dataset showcases influential works, emphasizing the impact of key publications in the field. Keywords: Accounting System, Supply Chain, Scholarly Works, Lens.org, Research Collaboration